The impact of municipal budgets and land-use management on the hazardous waste production of Malaga municipalities - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Jiménez-Madrid, Alberto (Elsevier, 2017)
Economic development and the search for competitiveness have become key issues in regions' economic success. However, despite the direct relationship between economic and environmental management, few land-use plans consider the latter aspect, and city managers delegate the responsibility for environmental impacts to state legislation and private initiatives. This myopic search for competitiveness has meant that a holistic view of environmental issues is often not integrated into municipal decision-making processes. Therefore, this study's objective was to determine the relevant direct and indirect relationships of land management and budgetary procedures of municipalities with overall production levels of hazardous waste. To this end, a primary tourist region, Málaga, was examined in terms of how this waste's environmental impacts can affect the region's vital tourism sector. This research used principal component analysis, regression by ordinary least squares, cluster analysis in two stages and a means test to compare the data for the Province of Malaga's subregions. The results confirm a positive relationship between municipal expenditure and waste production and highlight the environmental benefits of land use involving environmentally non-aggressive crops. The results also reveal a negative relationship between waste production and financial assets and a direct relationship between unproductive land and the production of hazardous waste. The findings also highlight the necessity of raising awareness about the need for collaboration between different agents, especially in the development of inter-municipal strategies.
https://openpolicyfinder.jisc.ac.uk/id/publication/12531
Keywords: Presupuestos municipales - Málaga; Depósitos de residuos peligrosos - Málaga; Gestión del medio ambiente - Aspectos económicos; Environmental plans; Land-use planning; Regional development; Municipal budgets; Hazardous waste; Cluster analysis